Theory of cyclic voltammetry in tubular electrodes under no flow conditions - Thompson, M; Davis, J; Compton, R (2006)
Numerical modelling of the concentration profile of the electroactive species within a tubular electrode under diffusion only conditions is used to simulate cyclic voltammetry experiments. Nernst conditions are assumed at the electrode surface. The simulated peak current is compared to that given by the Randles-Ševčík formula in order to determine the conditions of electrode size and voltage sweep rate under which there is no significant deviation from the Randles-Ševčík result. © 2005 Elsevier B.V. All rights reserved.